A rare case of leptomeningeal carcinomatosis in a patient with uveal melanoma: case report and review of literature. Issue 5 (October 2016) - Fedorenko, Inna V.; Evernden, Brittany; Kenchappa, Rajappa S.; Sahebjam, Solmaz; Ryzhova, Elena; Puskas, John; McIntosh, Linda; Caceres, Gisela; Magliocco, Anthony; Etame, Arnold; Harbour, J. William; Smalley, Keiran S.M.; et al.
Abstract : Uveal melanoma is a rare subtype of melanoma, accounting for only 3–5% of all melanoma cases in the USA. Although fewer than 4% of uveal melanoma patients present with metastasis at diagnosis, approximately half will develop metastasis, more than 90% of which disseminate to the liver. Infrequently, a number of malignancies can lead to leptomeningeal metastases, a devastating and terminal complication. In this case report, we present an exceedingly rare case of a patient with uveal melanoma who developed leptomeningeal carcinomatosis as the sole site of metastasis. After conventional methods to diagnose leptomeningeal carcinomatosis fell short, a diagnosis was confirmed on the basis of identification and genomic analysis of melanoma circulating tumor cells in the cerebrospinal fluid.